Is the interplay between self-efficacy and entrepreneurial intention gender-dependent? - Kurczewska, Agnieszka; Białek, Jacek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2014)
The aim of the study is to investigate whether the interplay between entrepreneurial intentions and self-efficacy depends on gender. As males still dominate worldwide in entrepreneurial activity, the authors are interested in the specifics of female entrepreneurship and its antecedents. The central hypothesis was that female students have lower self-efficacy than male students which induces lower intentions towards venture creation. To follow the research aims, the authors conducted a questionnaire among students at one of the Polish universities. It included questions relating to the concept of self-efficacy inspired by the works of Bandura (1977, 1982, 1986, 1989), Noble et al. (1999) and Boyd and Vozikis (1994). By using various statistical methods (including the two means t-test, the coefficient of correlation test, the Chi-squared independence test and the Mann-Whitney U test) the interplay between intentions, gender and self-efficacy was investigated. According to the findings, the level of entrepreneurial intentions is gender-dependent and men present higher intentions towards venture creation than women. However, entrepreneurial self-efficacy proved to be not related to gender and self-efficacy is not a major factor shaping entrepreneurial intentions. The reason for lower intentions among women is not significantly connected with their self-efficacy. The paper discusses the contextual meaning of the results and their implications for entrepreneurship education in Poland.
Argumenta Oeconomica, 2014, Nr 2 (33), s. 23-38
Keywords: entrepreneurial intentions; self-efficacy; entrepreneurial education; gender; Poland